Migration, mothering and schooling: a case study of Baltic mothers in Ireland - SABANOVA, INGA (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Sociology, 2020)
This thesis explores the parental involvement of Estonian, Latvian and Lithuanian mothers within and outside of formal schooling in Ireland. The number of Baltic families has significantly increased in Ireland in the last decade as a result of the post-2004 migration from new EU member states. Considering that many Baltic parents might be confronted with totally different parental practices in Irish schools, this thesis aims to explore the meanings Baltic mothers attribute to their experiences. To guide the research, the study uses Bourdieu's notion of habitus by emphasising the importance of dispositions that represent beliefs, ideas and practices in the understanding of capacity and limits of individual decisions. The case study methodology was chosen as the most appropriate way to explore the experiences of Baltic women as mothers and migrants in Ireland. The three main findings of this thesis are: first, culturally and historically specific dispositions play an important role in the ways Baltic migrant women perceive their maternal ideals and negotiate their everyday reality. Second, Baltic mothers utilise the resources available to them by simultaneously adopting strategies of 'fitting in' and 'standing out'. Finally, despite some differences based on their social class background, Baltic migrant mothers of both middle-class and working-class backgrounds expressed very similar approaches to their children's education and the way they envision their children's future trajectories in Ireland. Overall, this thesis adds new knowledge across several subfields of sociology, such as the sociology of education, migration studies and the sociology of family, both within the context of Ireland and the Baltic States. By combining different subfields of sociology, this research provides a more complete understanding of the meanings that Baltic mothers assign to their own practices in Ireland – matters that have never been explored before.
APPROVED
Keywords: Migration; Mothering; Baltic mothers; Parental involvement